Effects of photobiomodulation in the treatment of pressure sores (Research, Society and Development, 2021)
Pressure ulcers (PUs) are a cause of concern in health care institutions due to the negative effects they cause to patients, such as pain, infection, and delayed functional recovery. From this perspective, in order to accelerate wound healing, more current treatments are being explored. Among these treatments, the photobiomodulation (FBM) offered by low power laser therapy (LBP) stands out. Given the above, this paper aims to analyze the effects of photobiomodulation in the treatment of PUs. This is an integrative literature review, with searches carried out in MEDLINE, SCIELO and BDENF databases, in which complete papers were included, in Portuguese and English, available electronically and free of charge, published from 2015 to 2021 and that addressed the proposed theme. Studies that did not address the subject of interest or did not answer the guiding question were excluded, as well as duplicate publications in more than one database. The study was composed of the analysis of 8 publications. The findings showed that this therapy contributes to pain reduction, increases local vascularization and accelerates the process of tissue healing, favoring a positive evolution during the treatment of injuries. Thus, it is emphasized that the use of MBP is of paramount importance for the treatment of PUs, because when used in the correct manner, with a qualified professional, it presents positive results in the healing period of the lesion, regardless of the type of associated dressing.